Using probabilistic record linkage methods to identify Australian Indigenous women on the Queensland Pap Smear Register: the National Indigenous Cervical Screening Project. Issue 2 (12th February 2016) - Whop, Lisa J; Diaz, Abbey; Baade, Peter; Garvey, Gail; Cunningham, Joan; Brotherton, Julia M L; Canfell, Karen; Valery, Patricia C; O'Connell, Dianne L; Taylor, Catherine; Moore, Suzanne P; Condon, John R
Abstract : Objective: To evaluate the feasibility and reliability of record linkage of existing population-based data sets to determine Indigenous status among women receiving Pap smears. This method may allow for the first ever population measure of Australian Indigenous women's cervical screening participation rates. Setting/participants: A linked data set of women aged 20–69 in the Queensland Pap Smear Register (PSR; 1999–2011) and Queensland Cancer Registry (QCR; 1997–2010) formed the Initial Study Cohort. Two extracts (1995–2011) were taken from Queensland public hospitals data (Queensland Hospital Admitted Patient Data Collection, QHAPDC) for women, aged 20–69, who had ever been identified as Indigenous (extract 1) and had a diagnosis or procedure code relating to cervical cancer (extract 2). The Initial Study Cohort was linked to extract 1, and women with cervical cancer in the initial cohort were linked to extract 2. Outcome measures: The proportion of women in the Initial Cohort who linked with the extracts (true -pairs) is reported, as well as the proportion of potential pairs that required clerical review. After assigning Indigenous status from QHAPDC to the PSR, the proportion of women identified as Indigenous was calculated using 4 algorithms, and compared. Results: There were 28 872 women (2.1%) from the Initial Study Cohort who matched to an ever Indigenous record in extract 1 (n=76 831). Women with cervical cancer in the Initial Study Cohort linked to 1385 (71%) records in extract 2. The proportion of Indigenous women ranged from 2.00% to 2.08% when using different algorithms to define Indigenous status. The Final Study Cohort included 1 372 823 women (PSR n=1 374 401; QCR n=1955), and 5 062 118 records. Conclusions: Indigenous status in Queensland cervical screening data was successfully ascertained through record linkage, allowing for the crucial assessment of the current cervical screening programme for Indigenous women. Our study highlights the need to include Indigenous status on Pap smear request and report forms in any renewed and redesigned cervical screening programme in Australia.